2016
DOI: 10.7150/jca.15690
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Sensitizes Silymarin to Exert Synergistic Anticancer Activity in Colon Cancer Cells

Abstract: We studied combinatorial interactions of two phytochemicals, curcumin and silymarin, in their action against cancer cell proliferation. Curcumin is the major component of the spice turmeric. Silymarin is a bioactive component of milk thistle used as a protective supplement against liver disease. We studied antiproliferative effects of curcumin alone, silymarin alone and combinations of curcumin and silymarin using colon cancer cell lines (DLD-1, HCT116, LoVo). Curcumin inhibited colon cancer cell proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(29 citation statements)
references
References 35 publications
1
25
0
1
Order By: Relevance
“…It decreases polyp formation in APC Min/+ mice, inhibits cell proliferation, inflammation and angiogenesis, induces apoptosis, decreases beta-catenin levels (3), and targets colorectal cancer stem cells (4). Curcumin sensitizes silymarin to exert a synergistic anticancer activity on colon cancer cells (5). This is to our knowledge, the first case showing that curcumin followed by silibinin decreases colon polyp formation.…”
Section: Discussionmentioning
confidence: 52%
“…It decreases polyp formation in APC Min/+ mice, inhibits cell proliferation, inflammation and angiogenesis, induces apoptosis, decreases beta-catenin levels (3), and targets colorectal cancer stem cells (4). Curcumin sensitizes silymarin to exert a synergistic anticancer activity on colon cancer cells (5). This is to our knowledge, the first case showing that curcumin followed by silibinin decreases colon polyp formation.…”
Section: Discussionmentioning
confidence: 52%
“…Ranjbar et al showed that treatment of Ramos cancer cells with 100 µg/mL of sylimarin markedly increased the activity of caspase-3 [37]. Montgomery et al showed that silymarin at the highest dose of 100 µM/mL has antiproliferative activity in colorectal cancer cell lines: DLD-1, LoVo, and HCT116 [38]. Furthermore, the experiment carried out on the ovarian cell line indicates the inhibitory properties of silymarin: significantly limits the growth and rate of proliferation, inhibits the cell cycle in G1/S phase, and the doses of 50 µg/mL and 100 µg/mL activate the apoptotic pathway and induce cytochrome C release, as well as the reduction of the mitochondrial membrane potential [39].…”
Section: Discussionmentioning
confidence: 99%
“…While they are less toxic and have no side effects, combinatorial treatment of phytochemicals with chemotherapeutic agents can be an alternative method to reduce the dosage of traditional chemotherapeutic regimens and lower cardiac toxicity associated with them (50). Owing to drug resistance in cancer, curcumin has been shown to be an effective adjuvant in reversing chemoresistance and sensitizing cancer cells to chemotherapeutic drugs (4147,5154). …”
Section: Discussionmentioning
confidence: 99%